Congruity of Virtual Reality In-Game Advertising - Lupinek, Joshua M.; Yoo, Jinhee; Ohu, Eugene A.; Bownlee, Eric (Frontiers in Sports and Active Living, 2021)
The purpose of this conceptual article is to add a needed digital and interactive marketing research foundation with a new construct for activation of virtual reality (VR) in-game advertising (IGA). In July 2021 people with Oculus Quest headsets are scheduled to start seeing beta advertisements in virtual reality (Olson, 2021). IGA is not a new construct, but IGA in VR is as unique as this conceptual analysis since VR consumers have not yet experienced VR IGA intrusion. As this new consumer VR technology continues to disrupt traditional media as a $7.7 billion USD industry (Wood, 2020), that is expected to reach $57.55 billion by 2027 (Fortune Business Insights, 2021), marketing researchers must continue to evolve and understand the interdisciplinary VR research evolution as many VR users are likely to view IGA as intrusive. Topical areas of congruity of the IGA, interactivity of the IGA, intrusiveness of the IGA, realism of the experience, telepresence, brand awareness, and attitude toward the IGA are unraveled within the literature. Two main contributions of this article are the development of a VR In-Game Advertising Congruity Framework and a proper telepresence definition through review of the literature with a VR active participant context. This article aims to aid marketers in making informed IGA development decisions through strategic choice, via a centralized VR IGA congruity framework, that not only enhances brand awareness, but leaves participants with a favorable attitude toward the IGA to increase sales activation.